Genome-wide association study and candidate gene identification for the cold tolerance at the seedling stage of rapeseed (Brassica napus L.) - Guangyu Wu; Yanda Zhou; Jingyi Zhang; Mengjie Gong; Lixi Jiang; Yang Zhu (Crop Design)
Rapeseed (Brassica napus L.) is an important overwintering oilseed crop and suffers from severe cold stress during the seedling stage, due to the increasingly delayed sowing in the Yangtze river basin. However, the genetic basis underlying cold tolerance in rapeseed seedlings is not well understood. In this study, we observed the cold tolerance of 217 rapeseed accessions in the field and found a significant negative correlation between cold tolerance grades and malondialdehyde (MDA) content. A genome-wide association study (GWAS) of cold tolerance grades identified four significant loci in the genomic region of one MYB transcription factor BnaA8.MYB60. Furthermore, field accessions with BnaA8.MYB60 Hap1 exhibited significantly higher cold tolerance and lower expression of BnaA8.MYB60 compared to the majority of accessions with BnaA8.MYB60 Hap2. These results suggested that variation in the genomic sequences of BnaA8.MYB60 caused the divergence of gene expression levels and functions on cold tolerance in rapeseed seedlings. This study could provide the theoretical guidance for the breeding of cold-tolerant rapeseed varieties.